Harmony Beach Resort / Azreen Awang ... [et al.] - Awang, Azreen; Bashir Ahamad, Bibi Nurfaritha; Ahmad, Cik Som; Ab. Halim, Siti Noralisa (Malaysian Entrepreneurship Development Centre (MEDEC), 2001)
An entrepreneur is a person who undertakes to do a job. Entrepreneurship involves not only the process that leads to the setting up of a business entity but also the expansion and development of an on going concept. To be an entrepreneur as to start a business, a business plan is needed. Business plan is a written document which describe the proposed business or project to be undertaken in a comprehensive manner. For our business plan, we have decided to open up a resort named Harmony Beach Resort that will be located at Tok Bali, Pasir Puteh, Kelantan. We will provide the services such as accommodations, food and beverages, recreational and laundry services beside other facilities that are already provided around our resort. We hope by practising doing this business plan, we are encouraged to be a real entrepreneur in whatever types of business.